Emerging legislative and regulatory framework governing trade-related environmental issues : implications for Caricom countries. - STEWART, Taimoon (1996)
Focuses on the rapid emergence of environmental laws and regulations at the global level and in North America and Europe. Advises that adjustments which can affect a firm's competitiveness, particularly exports, are required in Caribbean countries.